Managerial Strategy of SP2DK for Value Added Tax (VAT) and Income Tax (PPH) Reporting - Budiyanto Budiyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
Hospitals operate as both public service institutions and business entities, requiring them to balance healthcare delivery with sound financial management and tax compliance. Although many core medical services are exempt from Value Added Tax (VAT), hospitals frequently conduct taxable commercial activities that create complexity in VAT and Income Tax (PPh) reporting. Differences in interpretation between hospitals and tax authorities often result in the issuance of a Letter of Request for Explanation of Data and/or Information (SP2DK), which functions as a supervisory and corrective instrument. This study aims to analyze managerial strategies adopted by private hospitals under the East Java Christian Church Health Foundation (GKJW) in responding to SP2DK related to VAT and Income Tax reporting. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis at three hospitals: Marsudi Waluyo Hospital (RSMW), Kristen Mojowarno Hospital (RSKM), and Mardi Waloeja Kauman Maternity and Children’s Hospital (RSIA Mardika). The findings indicate that effective SP2DK responses rely heavily on cross-functional coordination, improvement of tax literacy among staff, and the integration of accounting and tax information systems such as e-Faktur. The establishment of internal tax response teams, collaboration with external tax consultants, and active communication with tax authorities were found to significantly enhance reporting accuracy and response speed. However, challenges persist, including limited understanding of VAT regulations, non-integrated systems, delayed supplier tax invoices, and human resource constraints. Overall, the study demonstrates a shift in hospital tax management from reactive to proactive practices, positioning SP2DK as an organizational learning mechanism that strengthens compliance, accountability, and governance in faith-based healthcare institutions.